Teachers’ emotional health in neoliberalised education: sport, therapy, yoga and meditation as a new construction of “self-care” - Molina Pérez, Javier; Pulido-Montes, Cristina (Revista Española de Educación Comparada, 2024)
The emotional experience of teachers has proven essential to understand how the transformations introduced by the neoliberalisation agenda in education are managed. Various studies indicate that the dynamics of business management in education are having significant implications for emotional experiences. This research aims to understand the influence of educational neoliberalisation practices on teachers’ emotional experience. A qualitative methodological approach based on an inductive method following the Grounded Theory procedure is used. A theoretical sampling is defined, with the participation of 30 teachers of Compulsory Secondary Education and Baccalaureate in the Spanish context. The teachers’ narrative accounts are collected through a semi-structured in-depth interview and non-systematic recordings. It is found that emotional difficulties tend to appear in all the participants in this research. Different problems associated with stress, dissatisfaction or emotional tension were reported. To a lesser extent, mental health problems have been contrasted. Faced with this, teachers look for remedial solutions that allow them to enjoy a less damaging professional career. Rather than resisting the practices that generate their discomfort, teachers seek balances that help them to manage contradictory logi